Letter from Dr. John Torrey to James Curtis Booth - Torrey, John (1862)
Dr. John Torrey (1796-1873), Assayer of the United States Mint in New York, writes a letter of introduction on behalf of a Mr. Aufermann.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; United States. Assay Office, New York City